(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Today the English language is widely spoken throughout the world. It is the language of 21st century the language of informative technologies, so while describing the English language; first of all it should be underlined that the English language is the mother tongue of the global media. To understand English clearly one should know not only its standard vocabulary but also its different styles, dialects, proverbs, sayings, phrasal verbs and idioms, as they are used in any sphere: books, films, newspapers, formal speeches. One, looking through some papers, magazines and journals, will discover the same language to sound quite different, because he will find familiar words with unfamiliar meanings. He will face idioms, phrasal verbs etc.